Green Marketing Strategies : Enhancing Brand Image and Consumer Trust in Sustainable Development - Kumar, Arya; Mallick, Swapna Swarupa; Hota, Sweta Leena; Vasudevan, Asokan; Şimşek, Sidar Atalay (Prabandhan: Indian Journal of Management, 2025)
Purpose : The primary objective of this research was to delve into the influence of green brand image (GBI), transparency (TR), and green advertising receptivity (GAR) on green brand trust (GBT) and their subsequent impact on consumers’ purchase intentions (PIs) within the realm of green marketing in India. Design/Methodology/Approach : Data was collected via a structured survey from 277 Indian consumers and analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 3.0. The research was conceptualized through the stimulus–organism–response (SOR) framework, examining how stimuli like GBI, TR, and GAR influenced GBI as the organism, ultimately impacting the response. Findings : The results showed that GBT was positively influenced by GAR and GBI, which enhanced PI. TR and non-deception (ND) do not significantly impact GBI. ND strengthens the GAR–GBI link, while TR does not moderate GBI–GBT. Practical Implications : This study advised Indian green market companies to focus on strengthening GBI and GAR to build consumer trust and boost PIs while maintaining TR and avoiding deceptive practices. Originality/Value : This study added to the present literature by understanding the aspects inducing consumers’ trust in green brands in the Indian context. It also highlighted the importance of TR and ND in building consumer trust and emphasized the need for companies to align their green marketing strategies with consumer expectations.